Respuesta :

Answer:

2x - 3y = 18  (1)

5x + 9y = -10​   (2)

<=>

Multiply both sides of (1) by 5, and multiply both sides of (2) by 2, then:

10x - 15y = 90

10x + 18y = -20

Subtract (2) to (1):

=> 33y = -110 => y = -110/33

Substitute y back into (1):

=> 2*x - 3*(-110/33) = 18

=> 2*x + 10 = 18

=> 2*x = 8

=> x = 4

=> Solution: x = 4, y = -110/33

Hope this helps!

:)

Answer: x=4 y= -10/3

Step-by-step explanation:

Look at the attachment. It should explain.

Ver imagen Аноним
Ver imagen Аноним
ACCESS MORE